Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Korupsi Yang Dilakukan Oleh Banyak Orang Pada Kasus Putusan Nomor 6/Pid.Sus.TPK/2023/PT.Pdg - Putra, Vananda; Danil, Elwi; Zurnetti, Aria (Universitas Ekasakti, 2023)
The rise of criminal acts of corruption in Indonesia, and the very dangerous impacts they cause, can even destroy the socio-cultural, political, moral and legal pillars of national security, so in reality overcoming these disgraceful acts must be done in extraordinary ways, So it is appropriate to say that criminal acts of corruption are included in extraordinary crimes. No. Corruption is often committed jointly, criminal law already regulates criminal acts of joint conduct or what is called participation (deelneming). However, often in proving criminal acts of corruption, the prosecutor does not develop the existence of other perpetrators who can be held accountable. The problems in this research are 1) What is the form of error and criminal responsibility of each perpetrator in criminal acts of corruption committed by many people (Case Study Decision Number 6/Pid.Sus.TPK/2023/PT.Pdg 2) How is the Evidence in the Case Corruption committed by many people in Decision Number 6/Pid.Sus.TPK/2023/PT.Pdg. 3) What are the considerations of the Panel of Judges in Decision Number 6/Pid.Sus.TPK/2023/PT.Pdg? This type of research is normative juridical research, using a statutory and conceptual approach, with primary and secondary data collection techniques. Based on the results of research and discussion, the concept of criminal acts committed jointly in corruption crimes is if the criminal act of corruption is committed by more than one person or two more people who together have the intention or desire for the act to be carried out. The conclusion of this research is that the decision of the Padang High Court is correct, because it strengthens the decision of the Corruption Crime Court at the Padang District Court Number 46/Pid.Sus-TPK/2023/PN.Pdg, but the responsibility of other perpetrators who participated in the crime corruption in this case, still not held accountable.